Reconstruction of Islamic Economics Education Based on QS. Al-Jumu’ah:10: The Internalization of Spiritual Values in Muslim Work Ethics - Umayyatun (LP3M KH Yazid Karimullah Institute, 2026)
This study aims to analyze QS. Al-Jumu’ah:10 as a conceptual foundation for the development of Islamic economics education based on Qur’anic values, particularly in integrating spirituality, work ethics, and economic productivity. The research employs a qualitative approach with a library research design through thematic content analysis (maudhu’i tafsir). Data were collected from the Qur’an, classical and contemporary tafsir literature, as well as scholarly articles on Islamic work ethics and Islamic economics education published between 2023–2026. The findings indicate that QS. Al-Jumu’ah:10 constructs a balanced paradigm between worship and economic activity, positioning work as an act of worship grounded in divine consciousness. The study identifies three main values: spirituality, Islamic work ethic, and economic productivity, which together form an integrated epistemological framework for Islamic economics education. However, the implementation of these values in current Islamic economics education remains partial and tends to be overly technical, with limited internalization of spiritual dimensions. This study concludes that QS. Al-Jumu’ah:10 can serve as a philosophical and epistemological basis for reconstructing Islamic economics education toward a more holistic and value-based system. The implication of this study is the need for curriculum integration that emphasizes Qur’anic values, ethical formation, and spiritual awareness in economic learning.